Semiotika Mimikri Kromatik: Studi Komparatif Visual Politik Cuomo dan Mamdani NYC 2025 - Dewi Pugersari (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study analyzes the phenomenon of "chromatic mimicry" in digital visual identity as a political communication tool related to the 2025 New York City (NYC) mayoral election. The study's primary focus is the semiotic anomaly that emerged following Andrew Cuomo's initial campaign defeat, which resulted in him adopting the colors of his political opponent, Zohran Mamdani. This study uses a qualitative, descriptive-comparative approach with a diachronic analysis of six digital posters from the candidates' official Instagram accounts, selected purposively. The sample includes Zohran Mamdani's visual consistency phase, the pre-anomaly phase, and Andrew Cuomo's mimicry phase during the January-November 2025 election period. The six posters were analyzed using three theories: Gestalt principles of visual organization, Kress & van Leeuwen's Grammar of Visual Design, and Ted Brader's emotional rhetoric. The results show that Mamdani successfully created "Urban Vernacular Authenticity" by using electric blue and bright orange colors derived from everyday New York City infrastructure, such as the MetroCard, taxis, and bodegas. This creates consistent place-based identification. In contrast, Cuomo's mimicry approach was ineffective due to emotional dissonance. The use of bright colors, which convey enthusiasm, contradicted the message, which was dominated by anxiety appeals about crime. This resulted in an ambiguous visual message and perceptual dissonance with the candidate's image. The study confirms that color in digital politics functions as an active semiotic infrastructure. The effectiveness of political branding depends not only on the adoption of visual aesthetics, but also on the consistency between chromatic codes and the substance of the ideological narrative.